Analysis of economic forecasting in the post-epidemic era: evidence from China - Li, Xin (Scientific reports, 2023)
This paper presents a predictive analysis of the Chinese economy in the post-epidemic era. Five major public health emergencies historically similar to the COVID-19 epidemic are used as the control group, and a fuzzy mathematical model is applied to forecast and analyze China’s economy after the COVID-19 epidemic. The forecast results show that China’s overall economy will have recovered to the pre-epidemic level in about 1 year, with the fastest recovery in individual economic indicators, followed by government final consumption and imports, then CPI, fiscal revenue, exports and money supply, and the slowest recovery in employment. Finally, a combination of all the parties makes policies and recommendations for China’s economic and social development in the post-epidemic era.